Makna Baru Naskah di Era Ekonomi Kreatif: Dangding Haji Hasan Mustapa dalam Kaos - Jajang A Rohmana (Jurnal Lektur Keagamaan, 2018)
This study discusses the revitalization of Sundanese manuscripts in the formation of local cultural identity through creative economy of fashion industry in West Java. The main source is Sundanese manuscript of Haji Hasan Mustapa’s dangding (1852-1930) which is transfered into t-shirts design. Hasan Mustapa is a great Sundanese poet whose name is make into one of the street names in Bandung. Hasan Mustapa’s dangding t-shirts was really appreciated by its consumers from the Sundanese community and the observers of Hasan Mustapa’s thought. The design of Hasan Mustapa’s t-shirts has been a part of the new meaning of Sundanese literary script in the creative economy era of Indonesia. Through culture identity theory, the study confirm that anthropologically the manuscript can be transfered into any media. The t-shirts became an alternative media that represents an effort to strengthen the local culture as well as to indigenize religious values in contemporary Indonesia. Through the t-shirts design, Hasan Mustapa’s dangding manuscript can be disseminated into the Islamic public sphere. It significantly represents the so-called safari and cultural migrant as a form of local expression in the global era.Keywords: manuscript, dangding, t-shirts, distribution outlet, identity Kajian ini membahas revitalisasi naskah Sunda dalam pembentukan identitas budaya lokal melalui ekonomi kreatif industri fesyen di Jawa Barat. Sumber utamanya adalah teks naskah Sunda berupa puisi dangding Haji Hasan Mustapa (1852-1930) yang dialihmediakan ke dalam kaos. Hasan Mustapa adalah seorang bujangga Sunda terbesar yang namanya diabadikan sebagai salah satu nama jalan di Kota Bandung. Kaos dangding sufistik Hasan Mustapa mendapat apresiasi dari konsumen umumnya komunitas kesundaan dan pengkaji Hasan Mustapa. Desain kaos dangding Mustapa telah menjadi bagian dari pemaknaan baru naskah sastra Sunda di era ekonomi kreatif. Melalui perspektif teori identitas budaya, hasil kajian menegaskan bahwa secara antropologis, naskah dapat dimanfaatkan dalam media apapun seiring perkembangan zaman. Kaos menjadi sebuah media alternatif yang merepresentasikan upaya penguatan budaya lokal sekaligus indigenisasi nilai-nilai keagamaan di era Indonesia kontemporer. Melalui kaos pula naskah dangding Mustapa didiseminasikan dari manuskrip ke ruang publik. Ia secara signifikan mewakili apa yang disebut sebagai safari dan migransi budaya sebagai sebuah bentuk ekspresi lokal di era global.Kata kunci: naskah, dangding, kaos, distro, identitas